Practical optimization of AECS PF-2 plasma focus device for argon soft X-ray operation - Akel, M.; Lee, S. (Springer US, 2012)
For operation of the plasma focus in argon, a focus pinch compression temperature range of 1.4–5 keV (16.3 × 106–58.14 × 106 K) is found to be suitable for good yield of argon soft X-rays (SXR) Ysxr. This is based on reported temperature measurements of argon plasmas working at regime for X-ray output. Using this temperature window, numerical experiments have been investigated on AECS PF-2 plasma focus device with argon filling gas. The model was applied to characterize the 2.8 kJ plasma focus AECS PF-2. The optimum Ysxr was found to be 0.0035 J. Thus, we expect to increase the argon Ysxr of AECS PF-2, without changing the capacitor bank, merely by changing the electrode configuration and operating pressure. The Lee model code was also used to run numerical experiments on AECS PF-2 with argon gas for optimizing soft X-ray yield with reducing L0, varying z0 and ‘a’. From these numerical experiments we expect to increase the argon Ysxr of AECS PF-2 with reducing L0, from the present computed 0.0035 J at L0 = 270 nH to maximum value of near 0.082 J, with the corresponding efficiency is about 0.03%, at an achievable L0 = 10 nH.